REASONS FOR THE DEVELOPMENT OF INFLAMMATORY COMPLICATIONS IN INTRAUTERINE DEVICE CARRIERS - Sukharev, Anatoly; Kopytsia, Tetiana; Boyko, Volodymyr (Eastern Ukrainian Medical Journal, 2023)
Introduction. In the context of the deteriorating demographic situation in the country, the decline in the living standards of the majority of the population, the deterioration of their reproductive health, and family planning issues deserve special attention [1, 2, 9]. One of the methods of contraception, which is widely used by women of reproductive age, is intrauterine contraception [7, 8]. Worldwide, millions of women have been using the IUCD for over three decades as a highly effective, safe, and convenient form of contraception [4, 5]. However, in recent years, there has been a sharp increase in the number of complications associated with this method of contraception, the most dangerous of which, both at the time of administration and due to long-term consequences for the reproductive system of women, are inflammatory diseases [6, 10]. The aim of our study was to identify the risk factors for inflammatory complications in IUCD carriers. Methods. The study was conducted on the basis of the Municipal Non-Profit Institution "Clinical Perinatal Center of the Blessed Virgin Mary" in 2015–2021 years. In order to analyze the causes of the inflammatory complications in IUCD carriers, we examined 101 patients hospitalized at a specialized gynecological hospital for acute inflammatory processes of the uterus and appendages. Results. The control group consisted of 20 women who were carriers of the IUCD, registered in the dispensary in the city antenatal clinic. The average age of women was 22.2 years: from 19 to 45 years. The duration of IUCD usage ranged from 8 months to 6 years. The reason for hospitalization was pain in 98% of cases, fever in 92%, violation of the ovarian-menstrual cycle in 45%, a combination of symptoms and complaints in 96% of cases. In the hospital, the standard clinical, laboratory, immunological, and ultrasound examinations were repeatedly carried out. The causative agents of inflammatory diseases of the genitals were determined using bacteriological and PCR research methods. We revealed the association between the incidence of purulent-septic complications and the frequency of examinations performed before the introduction of the IUCD. Consequently, only 48 (59.4%) patients underwent a full clinical and laboratory examination; in the future, only 26 (25.7%) of the admitted patients were constantly observed in the antenatal clinic. Moreover, an analysis was made of the dependence between IUCD type, the duration of carriage, and the prevalence of inflammatory diseases of the female genital organs. Conclusions. Thus, there is reason to assume that the use of IUCDs, especially Copper Y Cu 380 for more than three years, in women of childbearing age is a risk factor for the occurrence of purulent-septic complications